Intensity modulated radiation therapy: A review of current practice and future outlooks. Issue 4 (October 2018) - Rehman, Jalil ur; Zahra,; Ahmad, Nisar; Khalid, Muhammad; Noor ul Huda Khan Asghar, H.M.; Gilani, Zaheer Abbas; Ullah, Irfan; Nasar, Gulfam; Akhtar, Malik Muhammad; Usmani, Muhammad Nauman
Abstract: Intensity Modulated Radiotherapy (IMRT) is a modern type of external beam radiotherapy that conforms high radiation dose to the target with minimum dose to the organs at risk (OARs), making it an embellishment of every developed institution. The earlier publications didn't have much proofs of the clinical superiority of IMRT over other radiotherapy techniques. It was considered a complicated and expensive treatment technique but the advent of modern treatment and imaging modalities have made its rapid clinical implementation unquestionable. Now IMRT have grown up, it is not the technique in which non uniform beam intensities were generated just by metal compensators, now it has multileaf collimators (MLCs), rotational fan and cone beam delivery systems and robotic arm linear accelerators to cure the life threatening cancer diseases. IMRT with all its advances have some limitations including its high cost, increased staff work, increased time for its planning, and risks of marginal misses.